Плавание: [сборник (составитель З. П. Фирсов]) - Фирсов Захарий Павлович (1979)
Экземпляры: КХ (20210927) / Инвентарный номер: 711256 / Сис.шифр: 797 / Авт.знак: П 37 / ГРНТИ: 77.29.34 / ББК: 75.717.5